The Impact of Exchange Rate on Inflation: A Case Study of The Gambia(1978-2016) - Lowe, Alieu Badara (European Scientific Journal, ESJ, 2019)
This paper focuses on developing stylized facts about the inflationary process in The Gambia, focusing particularly on the relationship between the exchange rate regime and the sources of inflation. It also examines several variables which policymakers believed have affected the level of inflation in The Gambia. The type of data used in this paper includes the time series data set which is collected from the period 1978-2016. Augmented Dickey-Fuller (ADF) test is used to examine whether a variable is integrated of which was proposed by Dickey and Fuller (1979). This paper employed the order of integration to test for stationarity and it was found out that both inflation and interest rates were stationary at levels. On the other hand, exchange rate and GDP were non-stationary at levels. In addition, Johansen co-integration test is used to explore the presence of a long-run relationship among the series. Findings show that there is no long-run relationship between the variable exchange rate and Inflation. Using annual data from 1978-2016, it was found that money growth and exchange rate change factors typically related to fiscal influences are far more important in countries with floating exchange rate regimes than in those with fixed exchange rates. Mitigating inflation has been a top agenda for every country that wants to achieve sustainable economic growth in which The Gambia is no exception. More especially, The Gambia being a small open economy exposed to other countries and price shifts in the world economy have a direct impact on The Gambian economy.